Determinants of Sharia Stock Prices: Financial Performance, Capital Structure, and Interest Rates - Sani Widaningsih; Ikaputera Waspada; Mayasari Mayasari (Global Research Collaboration, 2026)
This study examines the extent to which financial performance, capital structure, and interest rates influence sharia stock prices. Financial performance is represented by return on assets, current ratio, and cash flow from operations, while capital structure is measured by debt to equity ratio. Interest rates are incorporated as a macroeconomic factor, and firm size is included as a control variable. The study employs a quantitative approach using balanced panel data drawn from sharia compliant firms consistently included in a major Islamic stock index over the 2015 to 2024 period. The final sample consists of 220 firm year observations. Panel data estimation is conducted using the Random Effects Model, selected on the basis of model specification tests. The results show that current ratio and interest rates have a significant negative effect on sharia stock prices. In contrast, return on assets, debt to equity ratio, and cash flow from operations do not exhibit a significant effect. Firm size shows a marginal negative effect at the 10 percent significance level. These findings suggest that investors in sharia equity markets respond more strongly to liquidity conditions and monetary policy signals than to several other firm specific financial indicators. This study contributes to the Islamic capital market literature by integrating firm level fundamentals and macroeconomic variables within a panel data framework and by providing updated empirical evidence on the determinants of sharia stock prices.